Hexabenzocoronene–Benzimidazole Hybrid Architectures and Faraday Rotation of the First Hexabenzocoronene–Phthalocyanine - Rocha Ortiz, Antonia; Suleymanov, Abdusalom A.; Puhlmann, Pascal; Krischer, Dustin; Müller, Carolin; Zahn, Dirk; Swager, Timothy M.; Hirsch, Andreas (Angewandte Chemie International Edition, 2025)
The synthesis and characterization of a first example of a Ni-phthalocyanine (Pc) hybrid molecule carrying four hexa-peri-hexabenzocoronene (HBC) substituents and of three HBC-benzimidazole derivatives is reported. These π-electron rich chromophores exhibit a high molar absorption coefficient with extended absorption up to 460 nm. Particularly, HBC-Pc absorbs throughout most of the UV–vis range with the Pc Q-band located at 672 nm. This enables its investigation as a Faraday rotator where it displayed a remarkable Verdet constant of −1.4 × 105 deg T−1m−1 at 700 nm assigned to Faraday A-term activity. Electrochemical measurements supported by DFT calculations elucidated the electronic structure of the molecules together with excited state molecular orbital analysis using TDDFT. Here, HBC-Pc showed a HOMO/LUMO gap considerably lower than the other HBC-based compounds due to the introduction of the Pc scaffol

Molecular Dynamics Simulation of Silicone Oil Polymerization from Combined QM/MM Modeling - Puhlmann, Pascal; Zahn, Dirk (Polymers, 2024)
We outline a molecular simulation protocol for elucidating the formation of silicone oil from trimethlyl- and dimethlysilanediole precursor mixtures. While the fundamental condensation reactions are effectively described by quantum mechanical calculations, this is combined with molecular mechanics models in order to assess the extended relaxation processes. Within a small series of different precursor mixtures used as starting points, we demonstrate the evolution of the curing degree and heat formation in the course of polymer chain growth. Despite the increasing complexity of the amorphous agglomerate of polymer chains, our approach shows an appealing performance for tackling both elastic and viscous relaxation. Indeed, the finally obtained polymer systems feature 99% curing and thus offer realistic insights into the growth mechanisms of coexisting/competing polymer strands.
CRIS-Team Scopus Importer:2024-07-12
Keywords: molecular dynamics; polymerization mechanisms; silicone

Molecular Mechanisms of Silicone Network Formation: Bridging Scales from Curing Reactions to Percolation and Entanglement Analyses - Puhlmann, Pascal; Zahn, Dirk (Polymers, 2025)
The curing of silicone networks from dimethylsilanediol and methylsilanetriol chainbuilder–crosslinker precursor mixtures is investigated from combined quantum/molecular mechanics simulations. Upon screening different crosslinker content from 5 to 15%, we provide a series of atomic-resolution bulk models all featuring 98–99% curing degree, albeit at rather different arrangement of the chains and nodes, respectively. To elucidate the nm scale alignment of the polymer networks, we bridge scales from atomic simulation cells to graph theory and demonstrate the analyses of 3-dimensional percolation of -O-Si-O- bonds, polydimethylsiloxane branching characteristics and the interpenetration of loops. Our findings are discussed in the context of the available experimental data to relate heat of formation, curing degree and elastic properties to the molecular scale structural details—thus promoting the in-depth understanding of silicone resins.
CRIS-Team Scopus Importer:2025-10-31
Keywords: molecular dynamics; network analyses; polymerization mechanisms; silicone